Genetic diversity and re-classification of coffee (Coffea canephora Pierre ex A. Froehner) from South Western Nigeria through genotyping-by-sequencing-single nucleotide polymorphism analysis - Anagbogu, C.F.; Bhattacharjee, Ranjana; Ilori, C.O.; Tongyoo, P.; Dada, K.E.; Muyiwa, A.A.; Gepts, Paul L.; Beckles, D.M. (Springer, 2019)
Coffea canephora is an important economic crop in Nigeria, however, little is known about the diversity inherent within, and the genetic relationship among coffee grown and conserved in the country. We examined the genetic diversity and relatedness among 48 Coffea genotypes which included: (a) C. arabica, C. abeokutae, C. liberica, and C. stenophylla, (b) 14 C. canephora accessions conserved in the germplasm of Cocoa Research Institute of Nigeria (CRIN), and (c) 30 farmer-cultivated genotypes collected from South-Western Nigeria. By analyzing 433048 single nucleotide polymorphisms (SNPs) identified through genotyping-by-sequencing we discovered that previous characterizations of C. canephora based on morphological data were inconclusive. Here, we established the correct number of C. canephora varieties present in the CRIN genebank which was four and not six as previously described based on morphological characters. We found three distinct diversity structures within the C. canephora genepool that were dominated by a single genetic group determined from passport descriptors to most likely be of Congolese (Democratic Republic of Congo) origin. High uniformity was also found among the farmer-cultivated accessions with 99% of them representing C. canephora var. Niaouli as their ancestral background. The analysis showed that the genetic base of coffee germplasm in Nigeria is narrow compared to the large genetic diversity of C. canephora. Therefore, broadening this genetic base through future acquisition and hybridization is imperative. However, the relatively high genetic differentiation (FST estimate = 0.3037) identified between Java Robusta and Niaouli will be used as a starting point for our breeding program.